Stres pengasuhan dan peran coping pada ayah yang memiliki anak dengan spektrum autisme - I Gusti Ayu Shinta Dewi Prameswari; Adriana Soekandar Ginanjar; Gloryka Ednadita; Santy Yanuar Pranawati (Jurnal Psikologi Sosial, 2022)
The aim of this study is to understand parenting stress and coping strategies in fathers who have children with AS (autism spectrum). This research used a phenomenological qualitative approach. The data were collected using semi-structured interviews and observation of four fathers who have children with AS aged adolescent to young adult. The participants were obtained through snowballing sampling. The results showed that the fathers experienced stress from various challenges. The primary source of stress is financial because they are responsible for financing their children’s needs. To manage the stress, fathers used various coping strategies. They collaborated with their wives in the process of accepting their child-ren's condition and planning their education (dyadic coping). They also got closer to God, tried to have a positive view of the problems, and were grateful for the progress of their children (religious coping). Individual coping strategies are also used, such as planning, seeking in-formation (problem-focused coping) and regulating emotions, developing positive perception (emotion-focused coping). In particular, religion plays a vital role in the process of accepting the child's condition and finding happiness. This study may have implications for future stud-ies about parenting stress, especially in the father population of children with AS. In addition, fathers of children with AS need to improve their coping strategies and acquire social support from various sources to manage their stress.